2014
DOI: 10.1002/aenm.201401767
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Electrochemical Route to Access Amorphous Mixed‐Metal Hydroxides for Supercapacitor Electrode Materials

Abstract: mixed-metal hydroxide compounds such as Ni-Al, [ 3 ] Co-Ni, [4][5][6][7][8][9][10] Mn-Co, [ 11 ] Co-Ru, [ 12 ] Ni-Co-Cu, [ 13 ] and Ni-Co-Zn [ 14 ] have advantages over single-composition compounds as positive electrode materials for supercapacitors because mixed-metal compounds greatly promote the integrated electrochemical performance. [15][16][17][18] Almost all efforts in this fi eld have been directed towards crystalline mixed-metal hydroxide materials because these compounds have superior electrochemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
130
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(144 citation statements)
references
References 36 publications
8
130
0
Order By: Relevance
“…Moreover amorphous material possesses much more unsaturated ligand atoms and efficient electrochemically active sites compared to crystalline counterpart. 52 These features favour the charge transport process in the material. This is conrmed by the low interface charge transfer resistance and good rate ability of the Ba x Ni 3Àx (PO 4 ) 2 material shown above.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover amorphous material possesses much more unsaturated ligand atoms and efficient electrochemically active sites compared to crystalline counterpart. 52 These features favour the charge transport process in the material. This is conrmed by the low interface charge transfer resistance and good rate ability of the Ba x Ni 3Àx (PO 4 ) 2 material shown above.…”
Section: Resultsmentioning
confidence: 99%
“…Similar phenomenon has been reported by Li et al who found superior supercapacitive performance with a series of amorphous Ni-Co-Fe hydroxides. 52 It is ascribed to the unique nature of amorphous materials which is disorder in long-range but is structurally order in short-range. Moreover amorphous material possesses much more unsaturated ligand atoms and efficient electrochemically active sites compared to crystalline counterpart.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, crystallinity also plays an important role that amorphous electrochemically active materials usually possess better cycling stability because activation process is needed at the first several hundreds of cycles. 28 Amorphous structure can also endure the large structural changes during redox reactions well, leading to better cycling stability. Then, the effects of self-doping and crystallinity are optimized through changing the vulcanizing time.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Furthermore, pseudocapacitive properties may be improved through coincorporation of Ni and Co in the hydroxides to form Ni-Co double hydroxides, due to the possible valence interchange or charge hopping between Ni and Co cations. [1][2][3][4][5][6][7] Furthermore, pseudocapacitive properties may be improved through coincorporation of Ni and Co in the hydroxides to form Ni-Co double hydroxides, due to the possible valence interchange or charge hopping between Ni and Co cations.…”
Section: Introductionmentioning
confidence: 99%
“…1,4,6,[10][11][19][20] However, the specific Please do not adjust margins Please do not adjust margins capacitance of the ASCs will be restricted due to the limited specific capacitance of carbon anodes which store charges mainly through electric double layer. So asymmetric supercapacitors (ASCs) were usually assembled for nickel and cobalt hydroxides based materials to broaden their cell voltages.…”
Section: Introductionmentioning
confidence: 99%